Atrioventricular conduction disturbance as an early feature of Reiter's syndrome. Issue 12 (December 1988) - Haverman, J F; Van Albada-Kuipers, G A; Dohmen, H J; Dijkmans, B A
Abstract : Atrioventricular (A-V) conduction disturbances in Reiter's syndrome are usually described in longstanding disease. This report deals with two male patients with Reiter's syndrome who developed an A-V block early in the course of the disease. One of these patients developed a second degree A-V block, Wenckebach type, which has not been described before at an early stage of this syndrome.